Answer:
90000 srry if im wrong
Step-by-step explanation:
Answer:
<h3>
f(x) = x - 6</h3><h3>
g(x) = x - 5</h3>
Step-by-step explanation:
![\dfrac{x^2-8x+12}{x^2-7x+10}\\\\x^2-7x+10\ne0\ \iff\ x=\frac{7\pm\sqrt{49-40}}{2}\ne0\ \iff\ x\ne5\ \wedge\ x\ne2\\\\\\\dfrac{x^2-8x+12}{x^2-7x+10}=\dfrac{x^2-2x-6x+12}{x^2-2x-5x+10}=\dfrac{x(x-2)-6(x-2)}{x(x-2)-5(x-2)}=\\\\\\ =\dfrac{(x-2)(x-6)}{(x-2)(x-5)}=\dfrac{x-6}{x-5}\\\\\\f(x)=x-6\\\\g(x)=x-5](https://tex.z-dn.net/?f=%5Cdfrac%7Bx%5E2-8x%2B12%7D%7Bx%5E2-7x%2B10%7D%5C%5C%5C%5Cx%5E2-7x%2B10%5Cne0%5C%20%5Ciff%5C%20x%3D%5Cfrac%7B7%5Cpm%5Csqrt%7B49-40%7D%7D%7B2%7D%5Cne0%5C%20%5Ciff%5C%20x%5Cne5%5C%20%5Cwedge%5C%20x%5Cne2%5C%5C%5C%5C%5C%5C%5Cdfrac%7Bx%5E2-8x%2B12%7D%7Bx%5E2-7x%2B10%7D%3D%5Cdfrac%7Bx%5E2-2x-6x%2B12%7D%7Bx%5E2-2x-5x%2B10%7D%3D%5Cdfrac%7Bx%28x-2%29-6%28x-2%29%7D%7Bx%28x-2%29-5%28x-2%29%7D%3D%5C%5C%5C%5C%5C%5C%20%3D%5Cdfrac%7B%28x-2%29%28x-6%29%7D%7B%28x-2%29%28x-5%29%7D%3D%5Cdfrac%7Bx-6%7D%7Bx-5%7D%5C%5C%5C%5C%5C%5Cf%28x%29%3Dx-6%5C%5C%5C%5Cg%28x%29%3Dx-5)
Answer:100
Step-by-step explanation:
Expand
x = 150 - 0.5x
Add 0.5x to both sides
x + 0.5x = 150
Simplify x + 0.5x to 1.5x
1.5x = 150
Divide both sides by 1.5
x = 150/1.5
Simplify 150/1.5 to 100
x = 100
Answer:
41.23
Step-by-step explanation:
Mean = (23 + 50 + 49 + 48 + 49 + 32 + 37 + 40 + 41 + 42 + 41 + 41 + 43) ÷ 13
Mean = 536 ÷ 13 = 41.23 (rounded up to two decimal places)